Coronary computed tomography and triple rule out CT in patients with acute chest pain and an intermediate cardiac risk for acute coronary syndrome: Part 2: Economic aspects - Henzler, Thomas; Grüttner, Joachim; Meyer, Mathias; Apfaltrer, Paul; Borggrefe, Martin; Schönberg, Stefan; Fink, Christian (European journal of radiology, 2012)
Objective: To evaluate the economic impact of integrating coronary CT angiography (cCTA) or whole chest “triple-rule-out” CTA (TRO-CTA) in the work-up of patients with acute chest pain. Materials and methods: 100 consecutive emergency department patients with acute chest pain and an intermediate cardiac risk for ACS underwent cCTA or TRO-CTA (cCTA group). Diagnostic performance, rate and length of hospitalization, hospital costs, hospital reimbursement and hospital profit were analyzed. All findings were compared to those of 100 different patients with acute chest pain that were evaluated with a standard of care (SOC) diagnostic algorithm (SOC group) that did not include cCTA. Diagnostic performance (“safety”) of both algorithms was defined as the absence of major adverse cardiac events (MACE) over a 90-day follow-up period. Results: In the cCTA group 60/100 patients were safely discharged at the same day. 19/100 patients were hospitalized due to significant coronary stenosis on cCTA, which was confirmed by invasive coronary catheterization (ICC) in 17/19 patients. Relevant non-coronary disease that led to hospitalization were found in 21 patients of the cCTA group. In the SOC group all patients were hospitalized. 87 of these hospitalized patients underwent ICC for exclusion of coronary artery stenosis. A significant coronary artery stenosis was found in only 25 of these patients. Within the cCTA group no patient suffered from MACE over the 90-day follow-up period. In the SOC group 2 patients were rehospitalized during the 90-day follow-up period due to recurrent chest pain and 1 patient because of a pseudoaneurym of the left femoral artery after ICC. The median hospital costs per patient were significantly lower in the cCTA group than in the SOC group (428.9€ vs. 1575.0€, p<0.001). The median reimbursement of the cCTA group was less compared to the SOC group (589.8€ vs. 2412.1€, p<0.001) and patients in the cCTA group gained less profit than patients in the SOC group (57.0€ vs. 448.4€, p<0.001). Conclusion: Integrating cCTA or TRO-CTA in a SOC algorithm can safely reduce the number of hospitalized patients and reduce total health care costs.